INCREASING ENGLISH LANGUAGE KNOWLEDGE FROM READING COMPREHENSION EXERCISES - Rakhmanova Mukhayyo Nabijanovna (Scholar Express Journal, 2024)
Reading comprehension skills that allow students to process others’ writing so they can understand underlying messages and make insightful connections. These skills are extremely important for students’ successful development. Learning interactive and fun methods for helping students engage with their educational advancements
Keywords: Teaching methodology; teaching aims; pedagogical methodological character